2013
DOI: 10.1902/jop.2012.120547
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Stem Cells Possess the Characteristics of Pericytes

Abstract: PDLSCs possess pericyte-like characteristics and may localize as pericytes in the PDL. These data provide useful information for stem cell biology in periodontal research and stem cell-based periodontal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 33 publications
9
47
0
4
Order By: Relevance
“…The percentages of IdU + cells at the peritenon, mid-substance, and tendonbone junction excluding the hypertropic chondrocyte zone were counted and the expression of Ki67, a cell proliferation marker, in IdU + cells at different regions was compared after co-immunofluorescent staining. The co-localization of LRCs (stable IdU + cells) with pericytes at the peritenon, mid-substance, and tendon-bone junction excluding the hypertropic chondrocyte zone was also examined by coimmunofluorescent staining with a pericyte-related marker (CD146) [20]. The co-localization of LRCs with CD44 and Sca-1, two commonly used in vitro MSC markers, in the midsubstance in intact tendon and at the window wound at day 7 after injury (see protocol below) was examined by coimmunofluorescent staining.…”
Section: Methodsmentioning
confidence: 99%
“…The percentages of IdU + cells at the peritenon, mid-substance, and tendonbone junction excluding the hypertropic chondrocyte zone were counted and the expression of Ki67, a cell proliferation marker, in IdU + cells at different regions was compared after co-immunofluorescent staining. The co-localization of LRCs (stable IdU + cells) with pericytes at the peritenon, mid-substance, and tendon-bone junction excluding the hypertropic chondrocyte zone was also examined by coimmunofluorescent staining with a pericyte-related marker (CD146) [20]. The co-localization of LRCs with CD44 and Sca-1, two commonly used in vitro MSC markers, in the midsubstance in intact tendon and at the window wound at day 7 after injury (see protocol below) was examined by coimmunofluorescent staining.…”
Section: Methodsmentioning
confidence: 99%
“…33 Moreover, we observed that 32.9% hPDLSCs expressed CD146, which can be taken to interpret that PDLSCs located in the perivascular wall of periodontal ligaments and express pericyte-specific markers CD146. 34 MSCs derived from some other tissues (bone marrow, skin, liver, lung) also express CD146. 35 More importantly, PDLSCs exhibited the abilities to form bone/cementum-like mineralized tissue and ligament structures similar to Sharpey's fibers with an associated vasculature.…”
mentioning
confidence: 99%
“…NG2-expressing PCs per se serve as blood vessel progenitor cells [108,109] and can generate cardiomyocytes, smooth muscles and vascular EC in homeostatic conditions and after myocardial injuries for constitution of myocardium within the adult heart. Isolation and stimulation of PCs in adult heart may represent a potential therapeutic strategy to treat heart failures [110][111][112].…”
Section: Adult Cardiovascular Ng2 + Cells In Heart Failure Repairmentioning
confidence: 99%